OPTIMIZING THE USE OF ACCOUNTING MODULES AND ITS IMPACT ON THE LEARNING OUTCOMES - Nugraha, Abid Arya; Samsinar, Samsinar; Tikollah, M. Ridwan (Universitas Labuhanbatu, 2024)
This study aims to determine the effect of using the accounting module on learning outcomes in class XI Accounting at SMK Negeri 1 Makassar. The variable in this study is the use of the accounting module as the independent variable and student learning outcomes as the dependent variable. The population in this study were students of class XI Accounting. The sampling technique used the proportional-straltified random sampling technique, the sample from the population was selected randomly and proportionally with a sample of 57 students. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive percentage analysis, instrument test consisting of validity and reliability tests, hypothesis testing consisting of simple linear regression analysis, t-test and coefficient of determination using SPSS Version 26.00 for windows. Based on the results of the data analysis that has been done, the simple linear regression equation model Y = 6.466 + 0.312 X is obtained, which means that for each addition of 1 unit of use of the accounting module, student learning outcomes experience an increase of 0.312. While the results of the analysis of the coefficient of determination (r2) obtained the value of r2 = 0.529, this means that the effect of using the accounting module on student learning outcomes is 52.9% and the remaining 47.1% is influenced by other factors. While the results of the t-test analysis obtained a significant value of 0.000 <0.05, which means that the use of the accounting module has a significant effect on student learning outcomes, thus the hypothesis is accepted.